2021
DOI: 10.1136/bmjgh-2021-006069
|View full text |Cite
|
Sign up to set email alerts
|

Measuring oxygen access: lessons from health facility assessments in Lagos, Nigeria

Abstract: The COVID-19 pandemic has highlighted global oxygen system deficiencies and revealed gaps in how we understand and measure ‘oxygen access’. We present a case study on oxygen access from 58 health facilities in Lagos state, Nigeria. We found large differences in oxygen access between facilities (primary vs secondary, government vs private) and describe three key domains to consider when measuring oxygen access: availability, cost, use. Of 58 facilities surveyed, 8 (14%) of facilities had a functional pulse oxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Appropriate oxygen administration and monitoring of oxygen saturation are cost-effective measures for the management of pneumonia, and yet access to oxygen therapy is not a current standard indicator in the integrated GAPPD [ 2 , 19 ]. There is a need for more high-level data on oxygen use and monitoring to ensure that access to oxygen supply is being delivered in an effective manner [ 20 , 21 ]. Affordable access to uninterrupted oxygen supply should be a key indicator included in any assessment of standard ARI/pneumonia management.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate oxygen administration and monitoring of oxygen saturation are cost-effective measures for the management of pneumonia, and yet access to oxygen therapy is not a current standard indicator in the integrated GAPPD [ 2 , 19 ]. There is a need for more high-level data on oxygen use and monitoring to ensure that access to oxygen supply is being delivered in an effective manner [ 20 , 21 ]. Affordable access to uninterrupted oxygen supply should be a key indicator included in any assessment of standard ARI/pneumonia management.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcomes were (i) the proportion of children and neonates who were screened with pulse oximetry and (ii) the proportion of children and neonates with hypoxaemia (SpO 2 <90%) who received oxygen therapy. These outcomes were selected to be consistent with our primary stepped wedge trial analysis,26 and reflective of a patient-centred approach to measuring oxygen access 7…”
Section: Methodsmentioning
confidence: 99%
“…However, broken equipment is ubiquitous in many low-resource settings raising questions of how maintenance practices can be improved and sustained 17–19. We know that oxygen equipment and supplies are major costs for health systems, individual facilities and patients,7 17 20 21 but there are few data to support cost-effectiveness analyses or decisions 22–24…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, despite WHO primary care guidelines encouraging pulse oximetry screening for young children with respiratory illness, 9 pulse oximetry availability and use in primary care settings is rare. [10][11][12] Previous studies in Africa and Asia-Pacific regions have shown that very few HCWs in primary care facilities have pulse oximeters or are trained to use them, even though it is a simple and acceptable technology. [10][11][12][13][14][15] The COVID19 pandemic has brought overdue public urgency and awareness of the longstanding need to strengthen pulse oximetry and oxygen systems in healthcare facilities in low-and middle-income countries (LMICs) -but we have limited data to guide implementation in primary care settings.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Previous studies in Africa and Asia-Pacific regions have shown that very few HCWs in primary care facilities have pulse oximeters or are trained to use them, even though it is a simple and acceptable technology. [10][11][12][13][14][15] The COVID19 pandemic has brought overdue public urgency and awareness of the longstanding need to strengthen pulse oximetry and oxygen systems in healthcare facilities in low-and middle-income countries (LMICs) -but we have limited data to guide implementation in primary care settings. [16][17][18][19][20][21][22] Limited data suggests that pulse oximetry performed by primary care healthcare workers (HCWs) is feasible and can improve clinical decision-making and referral outcomes.…”
Section: Introductionmentioning
confidence: 99%